Making sense of coaching - Du Toit, Angelique (Los Angeles SAGE, 2014)
In her latest book, Angâelique du Toit goes beyond the techniques and goals explored in most coaching texts to examine the process of coaching and the importance of sense-making for creating meaning and encouraging self-reflection. In doing this, the coaching experience emerges as a type of transformational learning, in which the individual is guided through a journey of discovery and revelation. Theories are drawn together in a fresh and original way which will cause readers to question how coaching should be defined and practised. Book jacket.
Includes bibliographical references and index.
Keywords: Employees -- Coaching of